Fijai Dea Sandika PENERAPAN METODE COMPOSITE PERFORMANCE INDEX DALAM SISTEM PENDUKUNG KEPUTUSAN TINGKAT KEPUASAN MASYARAKAT TERHADAP PELAYANAN RUMAH SAKIT ASSYIFA KOTA MANNA BENGKULU SELATA - Fijai Dea Sandika; Siswanto Siswanto; Reno Supardi (UNIVED Press, 2024)
ABSTRAK The hospital is a comprehensive form of health service organization, as well as a public health referral center. Hospitals are required to provide health services that meet optimal service standards. Hospitals as agents of change are expected to provide excellent service to patients. To resolve the large number of public complaints regarding satisfaction with Assyifa Hospital, Manna City, South Bengkulu Regency, it is necessary to build a decision support system in improving services, so a Composite Performance Index method is needed, which is to find the most appropriate priority choices for community satisfaction using weighting. The Composite Performance Index method is used to solve various problems such as complaints, decision making, evaluation, and so on. There are four criteria in assessing hospital services, namely service procedures, information delivery, fairness of medical treatment, and comfort. Keywords: Decision support system, Composite Performance Index, visual basic net